Opportunities, Challenges, and Strategies in the Academic Transition to Higher Education After Grade 12: A Literature Review - Chhayna Cheng (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: The transition from high school to higher education is a pivotal milestone that significantly influences students' careers, academic growth, and personal development. However, many students struggle with academic stress, financial challenges, and adjusting to new learning environments. Objective: This study aims to provide a comprehensive review of the opportunities, challenges, and strategies involved in the academic transition to higher education after Grade 12, with a focus on how students can be supported through this process to ensure a smooth and successful transition. Method: A literature review methodology was employed, analyzing 103 scholarly articles published between 2020 and 2025. The review synthesized findings from various studies on academic transition, focusing on opportunities for career development, challenges such as financial stress and ICT limitations, and strategies for overcoming these challenges. Result: The review revealed that the transition provides opportunities for career development, digital literacy, and social networking. However, students face challenges including financial stress, academic workload, and adjustment difficulties. Effective strategies identified include enhancing self-regulation, ICT skills, and parental engagement. Conclusion: This study underscores the importance of adopting a comprehensive approach to supporting students during their transition to higher education. By addressing both opportunities and challenges and implementing targeted strategies, institutions can better facilitate students’ academic success and well-being. Contribution: This research contributes to the existing literature by offering a unified framework that integrates opportunities, challenges, and strategies in the academic transition, providing valuable insights for educators, policymakers, and future research on improving support systems for students transitioning to higher education